问题 解答题
(1)计算:
2
7
×(-3)2-
2
7
×6+10÷(-
7
2

(2)化简:3(3x2y-xy2)-[2(x2y-5xy2)-x2y]
(3)解方程:1-2(x-2)=3x-7
(4)解方程:
1-x
2
=
4x-1
3
-1.
答案

(1)

2
7
×(-3)2-
2
7
×6+10÷(-
7
2

=

2
7
×9-
2
7
×6+10×(-
2
7

=

2
7
×(9-6-10)

=

2
7
×(-7)

=-2;

(2)3(3x2y-xy2)-[2(x2y-5xy2)-x2y]

=9x2y-3xy2-(2x2y-10xy2-x2y)

=9x2y-3xy2-2x2y+10xy2+x2y

=(9-2+1)x2y+(-3+10)xy2

=8x2y+7xy2

(3)去括号得,1-2x+4=3x-7,

移项得,-2x-3x=-7-1-4,

合并同类项得,-5x=-12,

系数化为1得,x=

12
5

(4)去分母得,3(1-x)=2(4x-1)-6,

去括号得,3-3x=8x-2-6,

移项得,-3x-8x=-2-6-3,

合并同类项得,-11x=-11,

系数化为1得,x=1.

单项选择题
判断题